Dies irae : Kroniek van het requiem - Bergé, Pieter; Christiaens, Jan; Beirens, Maarten (Universitaire Pers Leuven, 2021)
The Requiem (or Death Mass) is one of the oldest and longest surviving genres in Western music history. For hundreds of years it only existed in its original Gregorian guise, but from about 1450 many great composers have been inspired to write masterly new funeral masses. Dies Irae introduces the reader to these masterpieces in an accessible manner, without any prior musical knowledge being required. After an introduction to the meaning and structure of the text and music of the ancient Latin Mass for the Dead, a chronicle in three parts follows that guides the reader through the history of the requiem. In separate chapters, all the great and well-known requiems are discussed (including by Mozart, Brahms, Verdi, Fauré, Britten and Webber), as well as some less popular but equally poignant works (such as the requiems by Ockeghem, Schütz, Weill, Ligeti, Stravinsky and Zimmermann). Each requiem is discussed according to a fixed pattern, so that the reader can freely browse through different periods and compositions: first each work is situated in music historically, followed by a short discussion of each part separately. By linking the discussions to one reference recording per work, the reader can immediately test the explanation against listening practice. Under the direction of Pieter Bergé, and with the cooperation of Jan Christiaens, all contributions to 'Dies Irae. Chronicle of the Requiem' written by authors who are teachers, researchers or alumnus affiliated with the Musicology research unit of KU Leuven.